A study on the iodised salt use pattern amongst the slum dwellers in Kolkata - Kundu, Sourav; Mandal, Tamasi; Sau, Arkaprabha; Bhakta, Ishita; Chatterjee, Arindam (International Journal Of Community Medicine And Public Health, 2020)
Background: Iodine deficiency disorders (IDD) are most important causes of preventable brain damage all over the world. Iodization of salt is used as a weapon to prevent IDD through national iodine deficiency disorders control programme and food safety and standards act, 2006 and regulations, 2011. Climatic condition, knowledge about storage and culinary practices pose a problem in maintaining adequate iodine level in salt at the consumer level. Methods: An observational, cross-sectional, descriptive study was carried out in the slum of Baghbazar under the service area of urban health and training centre, R.G. Kar medical college and hospital, Kolkata from 18 April to 30 April 2018. Households were chosen using simple random sampling and one adult representative from each household was interviewed with pre-designed pre-tested schedule. Results: 100% of the households were found to use iodised salt. 19.2% were aware that they were using iodised form of salt. 96.2% people keep the salt in covered container but only 7.7% of them knew that if kept uncovered iodine vaporises from salt. Moreover 40.4% of the respondents were found to keep salt open close to the oven during cooking with 86.5% of them not believing that this practice can have effect on the quality of the salt. Conclusions: Awareness regarding the effect of iodised salt on health, proper storage and use pattern should be initiated for desired sustainable change in practice and strict enforcement of law for curbing sale of non-iodised salt must be implemented so that IDD cease to be a serious public health problem.